Application Of Kufic Calligraphy In The Design Of Malaysian Mosque Qibla Wall - Al Abbasi, Ahmed Mohammed Yahya (2020)
Mosque design should not be viewed solely from the outside form, but it should also be considered for the efficient use of its interior. In almost all mosques constructed around the globe, Mihrab, which lies within the Qibla wall, has essential tasks in orienting the Muslim operations of prostration in the mosques towards the Ka'ba in Mecca while at the same time offering the Imam the room itself in congregations. Thus, the application of Kufic calligraphy in the design of Malaysian Qibla wall in mosques is the main focus in this study to classify the types of Kufic calligraphy since there was a lack of attention given to calligraphy ornamentation in Malaysian mosques. Specifically, there is a lack of research papers that focuses on the usage of Kufic calligraphy in the design of mosques in Malaysia. This study was carried out by employing a qualitative method as well as an observational survey method to collect data. An observational survey was carried out through onsite building surveys and analysis. Visits were made from zone to zone between October 2017 and January 2018 to collect the data from 15 mosques that were randomly selected in Kuala Lumpur, Pulau Pinang and Melaka, to obtain the information regarding this study. This thesis is a significant contribution to the subject of Islamic architecture in Malaysia. Furthermore, this study would inspire other Muslim artists in Malaysia to use the Kufic calligraphy in their work.